Hospitalizations in neonatal intensive care unit at Mahajanga: impacts on parents - Raveloharimino, Henintsoa N.; Razanamanana, Safidisoa N.; Randriamanga, Lovasoa R.; Rasamimanana, N. G.; Vonindrazana, Eudino J.; Rabesandratana, Norotiana H. (International Journal of Research in Medical Sciences, 2020)
Background: Experiencing a birth with a pathology imposes on parents a lot of frustration. Objectives of this study were to describe the general profiles of newborns and to describe the hospitalization’s psychosomatic impact on parents; in intensive care unit of the neonatalogy ward at the mother-child complex at the university Hospital Androva Mahajanga Madagascar. Methods: It was prospective descriptive study, by a survey of parents, among 3 months, from 01st May to 31th July. Results: Were included 102 newborns. Mains reasons of admission are low birth weigth (51.9%), prematurity (42.1%) and perinatal asphyxia (23.5%). One hundred mothers and 90 fathers had answered our survey. Sleep distturance (all parents), negative feelings (70% of fathers and 75% of mothers), depressed mood (52.2% of fathers and 78% of mothers) and guilt (25.5% of fathers and 58% of mothers) were the most prominent psycological manifestations among parents; then somatic manifestations as digestive, cardiovascular type; weight loss was objectified on 33% of fathers. Conclusions: Newborns’s hospitalization is a difficult situation for parents. Caregivers have an important role in enabling the family to build up.